التعليم القرآني ودوره في خفض صعوبات التعلم الأكاديمية لدى الأطفال في الطور الابتدائي - مركون, هبة (جامعة الوادي - University of Eloued, 2021)
هدفت هذه الدراسة إلى معرفة التعليم القراني ودوره في خفض صعوبات التعلم الاكاديمية للطفل في الطور الابتدائي، ومن أجل تحقيق هذا الهدف اعتمدنا المنهج الوصفي،واخترنا العينة بطريقة مقصودة والتي بلغت 50معلما يدرسون بالمدارس القرآنية، ولجمع المعلومات استخدمنا الاستبيان كأداة أساسية في البحث والملاحظة والمقابلة كأدوات مساعدة، والإستمارة تتألف من أربعة محاور: محور للبيانات الشخصية، والمحور الثاني التعليم القرآني وتطوير مهارة القراءة لطفل الطور الابتدائي، والمحور الثالث بعنوان التعليم القراني وتطوير مهارة الكتابة لدى الطفل، والمحور الرابع هو بعنوان التعليم القراني وتطوير مهارة الحساب لدى الطفل.وقمنا بتحليل البيانات التي تم جمعها من الميدان باستخدام معامل كا مربع للتطابق.وتوصلنا للنتائج التالية :-يساهم التعليم القرآني في تطوير مهارة القراءة لدى طفل الطور الابتدائي.-يساهم التعليم القرآني في تطوير مهارة الكتابة لطفل الطور الابتدائي.-يساهم التعليم القرآني في تطوير مهارة الحساب لطفل الطور الابتدائي . Abstract: This study aimed at knowing Quranic education and its role in reducing the academic learning difficulties of the child in the primary stage, and in order to achieve this goal we adopted the descriptive approach, and we chose the sample in an intended manner that amounted to 50 teachers studying in Qur’anic schools, and to collect information we used the form as a basic tool in research, observation and interview as an auxiliary tools. The questionnaire consists of four axes: a axis for personal data, the second axis is Qur’anic education and the development of reading skills for the primary school child, and the third axis is titled Qur’anic education and the development of writing skills for the child, and the fourth axis is titled Qur’anic education and the development of the child's numeracy skill. We analyzed the data that was done. He collected it from the field using the Ka-square coefficient for congruence. And we reached the following results: - Quranic education contributes to the development of the reading skill of the primary school child. - Qur’anic education contributes to developing the writing skill of the primary school child. - Qur’anic education contributes to the development of the arithmetic skill of the primary school child.
مقال
Keywords: التعليم القراني - المدارس القرانية-صعوبات التعلم -صعوبات التعلم الاكاديمية.; Quranic education - Quranic schools - learning difficulties - academic learning difficulties